2020
DOI: 10.1371/journal.pone.0241544
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of hospitalised patients with acute kidney injury and COVID-19

Abstract: Introduction COVID-19 has spread globally to now be considered a pandemic by the World Health Organisation. Initially patients appeared to have a respiratory limited disease but there are now increasing reports of multiple organ involvement including renal disease in association with COVID-19. We studied the development and outcomes of acute kidney injury (AKI) in patients with COVID-19, in a large multicultural city hospital trust in the UK, to better understand the role renal disease has in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 36 publications
4
46
0
Order By: Relevance
“…Our ICU admission and mortality rate of patients with AKI are similar to previous studies (9)(10)(11)(12)(13)(14)(15). We found that the severity of AKI among patients with CA-AKI was similar to patients with HA-AKI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our ICU admission and mortality rate of patients with AKI are similar to previous studies (9)(10)(11)(12)(13)(14)(15). We found that the severity of AKI among patients with CA-AKI was similar to patients with HA-AKI.…”
Section: Discussionsupporting
confidence: 89%
“…Coronavirus disease 2019 (COVID-19) (1, 2) caused by the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) is the worst public health disaster of the century, accounting for millions of infections and deaths globally. Hospital-acquired acute kidney injury (HA-AKI) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) is a frequent complication of COVID-19 that is associated with critical illness and increased mortality. Proposed mechanisms of AKI in patients with COVID-19 include volume depletion, hypotension, sepsis, cytokine storm, and direct viral-induced AKI, although the latter has not been proven (16).…”
Section: Introductionmentioning
confidence: 99%
“…Kidney dysfunction in COVID-19 has been demonstrated to be an independent risk factor for mortality in hospitalized patients [8,9]. The emerging risk factors for AKI in COVID-19 (COV-AKI) include male gender, African American race, hypertension, diabetes mellitus, and congestive heart failure [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for AKI in critical patients with COVID-19 vary according to the population. Older age, male gender, black race, obesity, diabetes, hypertension, heart failure, chronic kidney disease, leukocytosis, anemia, lymphopenia, increase in levels of serum inflammatory markers (D-dimer, PCR, and IL-6), and need for mechanical ventilation and vasoactive drugs as well as the use of angiotensin-converting enzyme inhibitors were associated with a higher risk of AKI development in COVID-19 critical patients (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Herein, chronic kidney disease was more frequent in patients who developed AKI (18.5 vs. 14.6%), however with no statistical significance.…”
Section: Discussionmentioning
confidence: 99%